D DETERMINANTS OF PURCHASE INTENTION TENDENCIES OF CAREER WOMEN ON GREEN PRODUCTS - Wenti Ayu Sunarjo (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Human concern for health has been increasing and requires business people to provide solutions to health problems through the marketing of green products. Gender and occupation are demographic factors that are thought to influence the purchase of green products. This study aims to examine the model that presents the influence of lifestyle, green products, and social media marketing on purchase intention in career women. The research method used is a survey. The quantitative approach is done by using a multiple regression model. Questionnaires were used to collect data on samples of consumers of green products in Central Java and the Special Region of Yogyakarta with 252 respondents, namely career women. The measurement scale uses a Likert scale. Data analysis using multiple linear regression analysis with questionnaires distributed online using google forms. The results of the study confirm that lifestyle, green products, and social media marketing are predictors of purchase intention on green products. The results show that social media marketing has a greater influence on purchase intention compared to a healthy lifestyle and the power of green products themselves. In addition, this study also discusses the implications of the findings and identifies areas for future research.